Surveillance of tilapia lake virus (TiLV) in diverse aquaculture systems of the Indian Sundarbans and adjoining regions in West Bengal, India - Snigdha Karmokar; Sanjoy Das; Leesa Priyadarsani; Gadadhar Dash; Abraham, T. Jawahar (Indian Journal of Fisheries, 2025)
The current study aimed to monitor the occurrence of tilapia lake virus (TiLV) in farmed tilapias in the Indian Sundarbans, an ecologically fragile world heritage site. Fifty-one samples comprising Oreochromis niloticus (n=41) and O. mossambicus (n=10) were collected from the surveyed farms, including 6 disease cases. In semi-nested PCR, 5.9 and 37.3% of the samples were positive in the 1st and 2nd step, respectively. TiLV was detected only in O. niloticus (46.3%) and 37.3% of the surveyed ponds. The two-step semi-nested PCR was more sensitive than the single-step SYBR green-based qPCR. The novel TiLV strains had similarities and close relations with TiLV CIFRI1 and CIFRI2 strains. Histologically, the diseased O. niloticus depicted typical TiLV alterations like syncytial hepatocytes. Developing and implementing good management practices and strict quarantine measures are necessary to combat the outbreak and spread of TiLV in the Indian Sundarbans. Keywords: Indian Sundarbans, Oreochromis niloticus, Oreochromis mossambicus, Syncytial hepatocytes, Tilapia lake virus